Bach’s “Fours” - Kira I. Yuzhak (Современные проблемы музыкознания)
The grouping of pieces is the matter of concern for both composers and researchers. For the former, it manifests itself already in the titles of collections, while for the latter it is an impetus for a comprehensive study of hidden mechanisms behind composers’ thinking. A.Milka in his article Bach’s Sixes (1999) identified several ways Bach approached the grouping of works. However, in his large cyclical opuses another “measure” stands out: the four, formed by canons (Die Kunst der Fuge) or duettos loaded by canonical work (Clavier Übung III). By way of a reminder, Bach’s canons are usually grouped by ten and/or four: Einige Canonische Verænderungen, BWV769, contains four contrapuntal canons (variations I–IV) and four thematic ones (variation V); Musicalisches Opfer features ten canons: six countrapunctal and four thematic; Verschiedene Canones, BWV1087, includes 14 canons written in groups of four, six and four canons. In fact, the grouping of four is not limited to Bach’s canons alone: he is known for numerous four-part suites and sonatas. So, it is not surprising that four orchestral suites, created in different years, were collected and numbered by W. Schmieder as a specific group of four. Research should focus on how Bach organises his compositions in groups of four, but also how, under the pressure of circumstances, he himself violates his plans (e.g., his engraving of Musicalisches Opfer and Die Kunst der Fuge). Whatever approach to grouping we take, a question begs itself: what provides diversity and what facilitates integrity? A.Milka answered this question through his analysis of the “sixes”. This article is an attempt to approach the Bach’s “fours”. The internal organisation of the “four” depends on its context: in a contrasting environment, it demonstrates the diversity of its components, in a balanced environment, it is organized in the order of the main technical characteristics. The functional and semantic content of the “fours” depends on how they are presented in a large cycle: together or in random order. In the first case, the highlight is the difference between the “four” and the pieces surrounding it. In the second case, it strengthens the structure of the whole, as its part, from inside.